Antiviral Activity of Isoimperatorin Against Influenza A Virus in vitro and its Inhibition of Neuraminidase - Lai, Yanni; Han, Tiantian; Zhan, Shaofeng; Jiang, Yong; Liu, Xiaohong; Li, Geng (Frontiers in Pharmacology, 2021)
Influenza A virus (IAV) poses a severe threat to human health and is a major public health problem worldwide. As global anti-influenza virus drug resistance has increased significantly, there is an urgent need to develop new antiviral drugs, especially drugs from natural products. Isoimperatorin, an active natural furanocoumarin, exhibits a broad range of pharmacologic activities including anticoagulant, analgesic, anti-inflammatory, antibacterial, anti-tumor, and other pharmacological effects, so it has attracted more and more attention. In this study, the antiviral and mechanistic effects of isoimperatorin on influenza A virus in vitro were studied. Isoimperatorin illustrated a broad-spectrum antiviral effect, especially against the A/FM/1/47 (H1N1), A/WSN/33 (H1N1, S31N, amantadine resistant), A/Puerto Rico/8/34 (H1N1), and A/Chicken/Guangdong/1996 (H9N2) virus strains. The experimental results of different administration modes showed that isoimperatorin had the best antiviral activity under the treatment mode. Further time-of-addition experiment results indicated that when isoimperatorin was added at the later stage of the virus replication cycle (6-8 h, 8-10 h), it exhibited an effective antiviral effect, and the virus yield was reduced by 81.4% and 84.6%, respectively. In addition, isoimperatorin had no effect on the expression of the three viral RNAs (mRNA, vRNA, and cRNA). Both the neuraminidase (NA) inhibition assay and CETSA demonstrated that isoimperatorin exerts an inhibitory effect on NA-mediated progeny virus release. The molecular docking experiment simulated the direct interaction between isoimperatorin and NA protein amino acid residues. In summary, isoimperatorin can be used as a potential agent for the prevention and treatment of influenza A virus.